Is Rice Supply Affected by Climate Change in East Java? - Amirusholihin, Amirusholihin; Rosandi, Dicky Auliya’ Akbar Hakim; Fernanda, Dandi; Khoiriyah, Eva Zunia (Universitas Gorontalo, 2025)
East Java Province is one of the provinces with a significant contribution to rice production in Indonesia. However, rice production in East Java experienced significant fluctuations from 2007 to 2020, with a noticeable decline from 2020 to 2021. This study aims to analyze the influence of climatic and non-climatic factors on rice production in East Java, using Time Series data from 1992 to 2023. The variables analyzed include rice harvest area, maximum annual temperature, minimum annual temperature, average temperature, and annual rainfall. The method used in this study is ARDL (Autoregressive Distributed Lag), which allows estimation of long-run and short-run cointegration relationships among the variables analyzed. The results show that the variable of harvest area has a positive influence on rice production in East Java, both in the short and long term. In addition, the variables of minimum temperature, maximum temperature, average temperature, and rainfall show a positive influence, but only in the long run. These findings indicate that both climatic and non-climatic factors play an important role in determining rice production in East Java. Therefore, managing the roles of the government and the community could be the key to increasing rice production in the future, while facing the challenges of increasingly dynamic climate change.